ASSESSMENT OF FUNCTIONAL IMPAIRMENT IN PATIENTS WITH LOW BACK PAIN - Ovdii, M. O. (Rehabilitation and Recreation, 2023)
Low back pain (LBP) ranks fifth in prevalence as a reason for seeking medical attention, affecting nearly 60–80 % of individuals during their lifetime. This issue involves specialists from various clinical fields and necessitates a multidisciplinary approach to treatment. Understanding the pathogenic mechanisms of LBP and the functional limitations it imposes enables the optimization of treatment approaches and the selection of necessary rehabilitation interventions. Objective – to assess the functional impairment of patients with LBP based on pain localization and neurological status. Materials. Rehabilitation assessment and questionnaire surveys were conducted on 138 individuals with LBP referred to the outpatient rehabilitation department. The Quebec Back Pain Disability Scale was employed for functional impairment assessment, and the Quebec Task Force Classification of Spinal Disorders was used for pain categorization based on location and the presence of neurological deficits. Results. The distribution of patients based on the Quebec Task Force Classification showed that 48 % had LBP without radiation and neurological deficits, 18 % had LBP radiating to the knee without neurological deficits, 14 % had LBP radiating below the knee without neurological deficits, 15 % had leg radiation with neurological deficits, and 5 % were post-operative cases within 6 months of surgery. According to the Quebec Back Pain Disability Scale, patients with LBP radiating into the leg and neurological deficits exhibited the highest level of functional impairment, scoring 29.2±12.7 points compared to other patients. Conclusions. The level of functional impairment in patients with LBP depends on pain intensity, pain localization, and the degree of neurological symptoms. Patients with LBP radiating into the leg and neurological deficits have a higher level of functional impairment compared to other patients.